IMPLEMENTASI BANTUAN LANGSUNG TUNAI (BLT) DANA DESA DI DESA BOTORECO KECAMATAN KUNDURAN KABUPATEN BLORA - Irma Dwi Damayanti; Amni Zarkasyi Rahman; Retna Hanani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
The Village Fund Direct Cash Assistance (BLT) is one of the efforts to deal with the impact of the COVID-19 pandemic which has been implemented at the rural level since 2020. The realization of the distribution of Direct Cash Assistance (BLT DD) in Botoreco Village only reached 6.1% of the 30% that should have been given to groups target. This study aims to analyze the process of implementing the Village Fund’s Direct Cash Assistance in Botoreco Village, Kunduran District, Blora Regency. In addition, to analyze the driving factors and inhibiting factors of the implementation process. This study uses the theory of policy implementation with the theoretical concepts of Donald Van Meter and Carl Van Horn to identify factors. This research also refers to the Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration Number 6 of 2020 and Regulation of the Regent of Blora Number 77 of 2022. This study uses descriptive qualitative methods with data collection technique s through interviews, literature study, and observation. The results showed that the Village Fund’s Direct Cash Assistance had been given in a timely manner to the target group, monitoring and evaluation were also carried out routinely. However, the data collection process carried out was not right on target. The realization of distribution has not been maximized because the village fund budget is used for village physical development. So that the Village Fund’s Direct Cash Assistance is only given to 25 recipients. The process of implementing the Village Fund’s Direct Cash Assistance in Botoreco Village is driven by policy resource factors and the characteristics of the implementing agency. In addition, the process of implementing the Village Fund’s Direct Cash Assistance in Botoreco Village was also hampered by standard factors and policy objectives; communication between organizations and implementation activities; environmental social, economic and political conditions; and the disposition of the implementor. Thus, suggestions that can be given include the need for adjustment of target criteria, the need for integrated data updates, routine assistance in the process of implementing the Village Fund’s Direct Cash Assistance, the village government needs to set a priority scale, especially in handling the impact of covid-19.